The epidemiology and clinical features of melioidosis in Far North Queensland: Implications for patient management. - James D Stewart; Simon Smith; Enzo Binotto; William J McBride; Bart J Currie; Josh Hanson (Public Library of Science (PLoS), 2017)
BACKGROUND:The epidemiology, clinical presentation and management of melioidosis vary around the world. It is essential to define the disease's local features to optimise its management. PRINCIPAL FINDINGS:Between 1998 and 2016 there were 197 cases of culture confirmed melioidosis in Far North Queensland; 154 (78%) presented in the December-April wet season. 145 (74%) patients were bacteraemic, 58 (29%) were admitted to the Intensive Care Unit and 27 (14%) died; nine (33%) of these deaths occurred within 48 hours of presentation. Pneumonia was the most frequent clinical finding, present in 101 (61%) of the 166 with available imaging. A recognised risk factor for melioidosis (diabetes, hazardous alcohol use, chronic renal disease, chronic lung disease, immunosuppression or malignancy) was present in 148 (91%) of 162 patients with complete comorbidity data. Despite representing only 9% of the region's population, Aboriginal and Torres Strait Island (ATSI) people comprised 59% of the cases. ATSI patients were younger than non-ATSI patients (median (interquartile range): 46 (38-56) years versus 59 (43-69) years (p<0.001) and had a higher case-fatality rate (22/117 (19%) versus 5/80 (6.3%) (p = 0.01)). In the 155 patients surviving the initial intensive intravenous phase of treatment, eleven (7.1%) had disease recurrence, despite the fact that nine (82%) of these patients had received prolonged intravenous therapy. Recurrence was usually due to inadequate source control or poor adherence to oral eradication therapy. The case fatality rate declined from 12/44 (27%) in the first five years of the study to 7/76 (9%) in the last five (p = 0.009), reflecting national improvements in sepsis management. CONCLUSIONS:Melioidosis in Far North Queensland is a seasonal, opportunistic infection of patients with specific comorbidities. The ATSI population bear the greatest burden of disease. Although the case-fatality rate is declining, deaths frequently occur early after hospitalisation, reinforcing the importance of prompt, targeted therapy in high-risk patients.